The thread : within the deliberative democracy labyrinth - Christakis, Alexander N.; Kakoulaki, Maria Z. (Emerald Publishing Limited, 2025)
The Thread: Within the Deliberative Democracy Labyrinth brings together the pioneering work of Alexander N. Christakis, the recent contributions of Maria Kakoulaki, and collaborative projects spanning five decades. It showcases the critical need for inclusive democratic processes to tackle complex issues in human systems. Through these writings, readers will understand how our pluralistic cultures and interdependent networks extend beyond familiar horizons and times. The book reflects on historical moments, like the post-World War II era, when visionary leaders foresaw the challenges of industrial consumption, planetary limits, and the rise of unaccountable regimes. Dr. Christakis and his colleagues have drawn from various disciplines to synthesize a dialogic approach for sustainable democracy. Democracy, akin to a delicate flower, thrives only through the goodwill of those who recognize our interconnectedness. This fragile bloom faces threats from argumentative debates, autocratic power brokers, and information overload. While goodwill is essential for democracy's survival, it is insufficient on its own. The 21st century demands innovative approaches to civic dialogue. In response, Dr. Christakis founded the Institute for 21st Century Agoras, developing the Structured Democratic Dialogue (Structured Dialogic Design) to restore and enhance democratic practices. This volume is a treasure trove of landmark essays, case studies, scholarly reflections, and methodological insights. It serves as a metaphorical life raft for navigating an uncertain future. For those who believe that changing the world requires transforming our dialogue, The Thread: Within the Deliberative Democracy Labyrinth offers a gateway to our shared future.
Includes index.
Keywords: Deliberative democracy.; Political Science -- Political Ideologies -- Democracy.; Political structures: democracy.; elektronické knihy; electronic books